Androgen‐responsive lncRNA LINC00304 promotes cell cycle and proliferation via regulating CCNA1. Issue 9 (23rd April 2019) - Zhang, Pu; Lu, Yali; Kong, Zhe; Zhang, Yalong; Fu, Fangqiu; Su, Xinya; Huang, Yan; Wan, Xuechao; Li, Yao
Abstract: Background: Long noncoding RNA (lncRNA) plays a vital role in the development of many diseases. The abnormal expression of lncRNA is closely related to the occurrence and development of different kinds of tumors including prostate cancer (PCa). Methods: Differentially expressed lncRNA LINC00304 was identified using a publicly available gene expression data set (GSE38241) and quantitative polymerase chain reaction validation. The Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analysis were used to predict the molecular function of LINC00304. A lncRNA microarray, bioinformatic analysis, and chromatin immunoprecipitation assay were carried out to verify the upstream androgen receptor (AR) signaling pathway. Subsequently, the function of LINC00304 was observed by a series of in vitro assays. Results: We observed higher expression of LINC00304 in PCa cells and samples compared with normal prostate cells and tissues. Functional analysis of LINC00304 showed it was related to regulating cell cycle process, cellular developmental process, and focal adhesion. Further, we identified androgen‐inhibited lncRNA, LINC00304 as a direct target of AR. A series of functional studies revealed that overexpression of LINC00304 could significantly promote cell proliferation and cell cycle progression in PCa cells. We also find that LINC00304 can significantly promote CCNA1 expression in PCa cells. Conclusions: Our results indicate that LINC00304 may represent a new diagnostic and therapeutic biomarker for PCa.